Fungal Guilds Reveal Ecological Redundancy in a Post-Mining Environment - Geisianny Moreira; Jefferson Brendon Almeida dos Reis; Elisa Catão Caldeira Pires; Cristine Chaves Barreto; Helson Mario Martins do Vale (Mining)
Mining significantly impacts terrestrial ecosystems despite its importance to the global economy. As part of soil ecosystems, fungi are highly responsive to environmental and human-induced drivers, shifting community composition and structure. Indeed, fungi play a key role in maintaining ecosystem resilience. Thus, we aim to address the question of whether soil fungal communities maintain similar ecological functions despite changes in community composition due to the impact of mining across ecosystems. To evaluate the ecological role of fungi across four ecosystems with varying iron mining impact levels, we used the FUNGuild database to assign functional guilds at the genus level. Co-occurrence network and ordination analyses were used to infer ecological relationships among fungal taxa and visualize the correlation between edaphic properties and fungal communities. A total of 22 functional guilds were identified, with dung saprotrophs, wood saprotrophs, fungal parasites, plant pathogens, ectomycorrhizal fungi, animal pathogens, and endophytes being the most abundant. Soil properties such as pH, organic matter, texture, and nutrients drive taxonomic and functional shifts. Our findings indicate that while mining activities shift fungal community compositions across ecosystems, the profiles of functional guilds show overlap between highly, moderately, and lowly impacted ecosystems, indicating functional redundancy. Network analysis reveals that highly connected hub taxa contribute to ecological redundancy across ecosystems and might act as a buffer against environmental disturbances. Our findings emphasize the important ecological role of soil fungi and indicate a potential for using fungal communities as bioindicators of ecological recovery in post-mining landscapes. From a mining and restoration perspective, this offers a low-cost, ecologically meaningful tool for monitoring soil recovery and guiding reclamation efforts.